PENGEMBANGAN MODEL KEILMUAN BIMBINGAN DAN KONSELING ISLAM MELALUI JURNAL HISBAH: JURNAL BIMBINGAN KONSELING DAN DAKWAH ISLAM - A Said Hasan Basri; Zaen Musyirifin; Moh Khoerul Anwar; Hayatul Khairul Rahmat (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2019)
Islamic guidance and counseling is very important in the current era of globalization. One interesting phenomenon in the development of modern science today is the emergence of scientific discourse related to the position and scientific map of Islamic guidance and counseling. The offense of Islamic guidance and counseling with several other disciplines actually places Islamic guidance and counseling in a fairly conflictual position. Although the Da'wah and Communication Faculties are not educational fields, the orientation of the scientific application of Islamic Guidance and Counseling can be applied to all backgrounds of life, both education and society. Therefore the development of a scientific model of Islamic guidance and counseling needs to be done. This study uses a qualitative descriptive research method. From the results of data collection, it is known that the scientific development of Islamic guidance and counseling is related to the model of education counseling and counseling, psychological guidance and counseling and counseling with the values of da'wah.